Anais Do XX Congresso Brasileiro De Engenharia Química 2015
DOI: 10.5151/chemeng-cobeq2014-0390-25724-159020
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Casca De Passiflora Edulis Como Fonte De Flavonóides

Abstract: formulações industriais é limitada devido à baixa solubilidade em meios lipofílicos. A esterificação por lipases tem sido utilizada para melhorar as propriedades dos flavonoides. Desta forma, avaliou-se a espécie Passiflora edulis (maracujá) como matéria-prima para obtenção de flavonoides que serão submetidos à esterificação utilizando lipase de Candida antarctica tipo B (CALB) imobilizada em nanoparticulas magnéticas e cujos resultados serão comparados com CALB imobilizada em resina acrílica comercial. Os ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Boa parte desses benefícios gerados por essas substancias se da pela capacidade inibidora ou de retardamento das reações de diversas espécies oxidantes, como radicais hidroxil, peroxi dentre outros. (SANDHAR et al, 2011;SOUSA et al, 2015;ARENAS-CHAVES et al, 2018)…”
Section: Tabela 03 -Resultados Dos Compostos Bioativos Da Polpa De Bacaba Paraenseunclassified
“…Boa parte desses benefícios gerados por essas substancias se da pela capacidade inibidora ou de retardamento das reações de diversas espécies oxidantes, como radicais hidroxil, peroxi dentre outros. (SANDHAR et al, 2011;SOUSA et al, 2015;ARENAS-CHAVES et al, 2018)…”
Section: Tabela 03 -Resultados Dos Compostos Bioativos Da Polpa De Bacaba Paraenseunclassified
“…Flavonoids represent a group of naturally diverse polyphenols involved in the chemical defense of plants against various predators. They are widely known and studied because of their innumerable biological activities that confer beneficial effects on human health [6]. Several studies have shown the existence of more than 4000 types of flavonoids, being divided into flavonoids, flavones, catechins, flavanones, anthocyanins, and chalcones [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the existence of more than 4000 types of flavonoids, being divided into flavonoids, flavones, catechins, flavanones, anthocyanins, and chalcones [7]. Among the numerous functions of flavonoids is the antioxidant activity, which is due to its sequestering action of free radicals and by chelating metal ions, in this way are able to protect the tissues of free radicals and lipid peroxidation [5,6,7]. Several structural forms are found in flavonoids, but their basic structure consists of fifteen carbon atoms in their nucleus, arranged in three rings (C6-C3-C6), two substituted phenol rings (A and B), and one pyran (heterocyclic C chain) coupled to ring A.…”
Section: Introductionmentioning
confidence: 99%